Analyse du balisage d’un itinéraire culturel du Conseil de l’Europe : l’exemple de la Via Francigena sur quatre tronçons en Suisse et en Italie - Éric Masson; Maryvonne Prévot (Netcom)
The Via Francigena (VF) is the pilgrimage route taken by Sigéric, the Archbishop of Canterbury to travel to Rome during the 10th Century. It became one of the European Council’s Cultural Route in 1994. The aim of this paper is to analyze the trail markers from the ground. These graphical traces are left by national/regional or local stakeholders involved in the management of the complex integration of natural or religious, tangible or intangible Heritage features in the urban trans-boundary landscapes of Martigny (Switzerland), Aoste, and Rome (Italy). Thus, we performed a transnational urban landscapes’ reading by means of a Carnet de Voyage enhanced and upgraded by a digital data collection including photos and GPS tags in order to carry out an exhaustive inventory of the trail markers along four sections of the Via Francigena. Those primary raw data were qualitatively analysed and classified using a thematical typology. Those data have also been used to calculate a linear density of trailmarkers which informs about the linear context of each inventoried GPS point. The diversity of the surveyed items and their complex organization showed the existence of both collaborative and competitive “graphical and informational ecology”. Increasing their visibility can be considered as a territorial power game between the various stakeholders concerned. Trail markers can therefore be considered as a governance arrangement established by the various territorial authorities (municipalities, Region, European Council) under the lead of the European Association of Via Francigena Ways (EAVF).